Scientific Publications in Nepal - Magar, A (Journal of Nepal Health Research Council, 2013)
Scientific publications have become a mainstay of communication among readers, academicians, researchers and scientists worldwide. Although, its existence dates back to 17th century in the West, Nepal is still struggling to take few steps towards improving its local science for last 50 years. Since the start of the first medical journal in 1963, the challenges remains as it were decades back regarding role of authors, peer reviewers, editors and even publishers in Nepal. Although, there has been some development in terms of the number of articles being published and appearances of the journals, yet there is a long way to go. This article analyzes the past and present scenario, and future perspective for scientific publications in Nepal. Keywords: ethics; journal; Nepal; publication; research; science.